Gerakan Transnasional Kristen: Wajah Ekonomi-Politik Agama dan Pendidikan di Indonesia - Elia Tambunan (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2019)
Although a number of prominent Church declared the Western imperialism and colonialism is not at all played an important role in the diffusion of the Christian religion and education in Indonesia, this paper, with a historical approach, read resource Indonesianis, Church, Islam, interviews and explanations of Christian figures competent in certain meetings, finds other things. The Christianization of Indonesia conducted through education is the historical fact of transnational movement of Christianity in Indonesia. The movement was a religious and educational shows by State actors and non-State since the days of colonialism and imperialism of Western mutual intertwinly. It's never "sterile" from the interests of the people and organizations concerning economic matters and politics.These findings contribute to the transnational studies by entering a transnational movement of Christians from Indonesia that has been more popular for the study of transnational Islamic movement or the transnational movement of world religions. This can be seen as a momentum to the start of the transnational movement studies in Christian Theological Seminary, Institute, and the Christian University in Indonesia. Meskipun sejumlah tokoh gereja menyatakan kolonialisme dan imperialisme Barat sama sekali tidak berperan penting dalam difusi agama dan pendidikan Kristen di Indonesia, tulisan ini dengan pendekatan historis membaca sumber Indonesianis, gereja, Islam, wawancara dan penjelasan tokoh Kristen berkompeten di pertemuan tertentu menemukan hal lain. Kristenisasi Indonesia yang dilakukan lewat pendidikan merupakan fakta historis adanya gerakan transnasional Kristen di Indonesia. Gerakan itu memperlihatkan agama dan pendidikan oleh aktor negara dan non-negara sejak zaman kolonialisme dan imperialisme Barat saling anyam-mengayam. Itu tidak pernah “steril” dari kepentingan umat dan organisasi menyangkut hal-hal ekonomi dan politik. Temuan ini berkontribusi untuk studi transnasional dengan memasukkan gerakan transnasional Kristen dari Indonesia yang selama ini lebih popular untuk kajian gerakan Islam transnasional ataupun gerakan transnasional agama dunia. Ini bisa dilihat sebagai momentum dimulainya studi-studi gerakan transnasional di Sekolah Tinggi Teologi, Institute, dan Universitas Kristen di Indonesia.